2014
DOI: 10.5539/jfr.v3n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Hydroethanolic Extracts of Solanum scabrum and Cola verticillata Against Cyclophosphamide Induced Toxicity in Female Rats

Abstract: The aim of this study was to evaluate the protective effects of hydroethanolic extracts of S. scabrum and C. verticillata against cyclophosphamide induced toxicity. In this light, female albino wistar rats were treated by intraperitoneal administration of 100 mg/kg BW of cyclophosphamide or distilled water every other day for 7 days associated with oral gavage using hydroethanolic extract of C. verticillata/S. scabrum at a dose of 200 or 400 mg/kg BW or not every day for the same 7 days. On the 8th day, blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…No que tange os resultados obtidos, a CYP induziu a diminuição significativa na dose de 100 mg kg -1 (P < 0,05) na atividade da enzima da catalase no tecido hepático, isso porque o aumento das espécies reativas causados pela CYP demanda muito das enzimas antioxidantes, podendo acarretar na diminuição das mesmas (ANGIE et al, 2014). Igualmente foi observada a diminuição significativa (P < 0,05) do conteúdo da GSH no tecido hepático, substância esta reconhecida como o antioxidante mais afetado pelos metabólitos tóxicos da ciclofosfamida, pois liga-se à acroleína (metabólito gerado pela CYP) de forma irreversível, inativando-a (MOGHE et al, 2015).…”
Section: Discussionunclassified
“…No que tange os resultados obtidos, a CYP induziu a diminuição significativa na dose de 100 mg kg -1 (P < 0,05) na atividade da enzima da catalase no tecido hepático, isso porque o aumento das espécies reativas causados pela CYP demanda muito das enzimas antioxidantes, podendo acarretar na diminuição das mesmas (ANGIE et al, 2014). Igualmente foi observada a diminuição significativa (P < 0,05) do conteúdo da GSH no tecido hepático, substância esta reconhecida como o antioxidante mais afetado pelos metabólitos tóxicos da ciclofosfamida, pois liga-se à acroleína (metabólito gerado pela CYP) de forma irreversível, inativando-a (MOGHE et al, 2015).…”
Section: Discussionunclassified
“…In Asia, some decaffeinated extracts are thought to be responsible for their anti-inflammatory and chemopreventive properties through their action on androgenic receptors (Bureau, 2013). Studies carried out on Cola verticillata showed, antiproliferative and anti-toxic properties of this species (Mbong et al, 2013(Mbong et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%